TREATMENT OF SEEDING TUBER CLOSING AND FUNGICIDE IMMERSION ON GROWTH AND PRODUCTION OF POTATO PLANTS (Solanum tuberosum L) - MERIKSA SEMBIRING (CV KULTURA DIGITAL MEDIA, 2022)
This research was conducted at BBI Kuta Gadung Berastagi, aims to: . a. To determine the effect of seed tuber division on the growth and production of potato plants. b. To determine the effect of soaking Functionda solution on the growth and production of potato plants and c. This study aims to determine the interaction between potato seed tuber division and Functiona solution on growth and production. The experimental design that will be carried out in this study is a factorial randomized block design (RAK). The first factor was the potato seed tuber division test (Y) consisting of Yo (without division), Y1 (splitting into 2), Y2 (splitting into 4). Factor II is testing the fungicide dose (D) consisting of Do (without fungicide), D1 (1g/lt water), D2 (3 g/lt water) and D3 (6 g/lt water). Based on the results of the research conducted, it can be seen that the use of seed tuber division gave a significantly different effect (p > 0.05) on plant height growth at 5 and 6 mst, Production (per sample and plot) and as seed the best was without division (Yo . The use of fungicide dose (D) also had a significantly different effect (p > 0.05) on plant height growth (5 and 6 wt.) and production.The effect of treatment combinations based on the analysis did not show a significantly different effect (p < 0.05) and as a recommended dose. The method used was a combination of seeds without division and the use of fungicides at 3 g/l water (YoD2).